Warm-up breathing exercises accelerate VO2 kinetics and reduce subjective strain during incremental cycling exercise in adolescents - Bahenský, P.; Marko, D.; Grosicki, G. J.; Malátová, R. (Journal of Physical Education and Sport, 2020)
Background: Breathing exercises based on the Wim Hof method, which is a combination of deep breathing and breath holds, increase arterial CO2 concentration. (i.e., hypercapnia). Induction of hypercapnia prior to exercise is purported to elicit a sympathetic response, leading to an increase in tidal volume and elevated blood flow to skeletal muscle in a manner that may improve exercise performance. We evaluated whether pre-exercise breathing techniques may impact VO2 kinetics during incremental cycling exercise. Methods: 16 adolescent (16.6±1.4 years) middle- and long-distance runners (8 males and 8 females) participated in our study. Participants performed two incremental cycle ergometer testing sessions consisting of two minute stages at 1, 2, 3, and 4 W·kg-1, which were immediately preceded by either a series of deep breathing exercises and breath holdsbased on each participant`s CO2 tolerance, or an equal duration of seated rest, the order of which was randomized. Heart rate, oxygen consumption, and respiratory parameters were continually assessed throughout the cycle ergometer tests and session rating of perceived exertion (Borg scale) was obtained at the end of the test. Results: Whereas all participants completed the final testing stage (4 W·kg-1) during the session preceded by breathing exercises, five participants were unable to complete this testing stage in the control trial. Oxygen consumption was significantly greater during the testing stages preceded by the breathing techniques (2.4-4.9%; p<0.05) and perceived effort throughout the training session was attenuated (18.5±1.2 vs. 17.4±1.1; p<0.01) following breathing exercises.All participants completed the final testing stage preceded by breathing exercises.Without breathing exercises five participants were unable to complete this stage. Conclusions: Breathing exercises, incorporating deep breathing and breath holds, performed prior to an acute exercise bout appears to accelerate VO2 kinetics and reduces subjective strain in young endurance athletes.